Some Issues Related to the Accrual of Age Pension in Uzbekistan and Ways to Solve Them - Shavkatovna, Sabirova Lola; Kabilovna, Shaislamova Nargiza (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article explores the demographic and economic factors influencing Uzbekistan's pension system, including economic employment, retirement age, life expectancy, and family-related trends such as marriage, divorce, and birth rates. It also considers the cultural traditions and mentality of the Uzbek population, which significantly impact the system's development. Adopting a qualitative approach, the study analyzes the existing methodology for calculating old-age pensions and its alignment with demographic and socio-economic realities. The findings highlight that demographic characteristics and economic conditions, such as employment rates and population structure, contribute to disparities in pension provision. Additionally, cultural norms and traditions play a role in shaping public expectations of the pension system. The article identifies shortcomings in the current methodology for pension calculation, particularly in addressing socio-economic justice. Proposals are made to enhance fairness, recognize unpaid work, and improve transparency in the pension system. The study underscores the need for reforms to align Uzbekistan's pension system with the socio-economic and demographic context, ensuring greater equity and sustainability.